Identification and Analysis of the Causes of Problems in the Implementation Stage of Construction Projects with APBD Funding Sources in West Sumatra Province - Parta Wijaya, Yan; Guspari, Oni; Rahma Wijaya, Suci; Andriyani, Dewi (JOELS: Journal of Election and Leadership, 2023)
Aims to determine and analyze the causes of problems that often arise at the implementation stage of construction projects with APBD funding sources in West Sumatra Province. The research method used is descriptive qualitative research, data collection through interviews, field observations and analysis of related documents. This research revealed several main causes of these problems, including a lack of thorough planning, frequent design changes, and problems in supervision and coordination between related parties. The results of this research can provide valuable insight for the West Sumatra Provincial Government in increasing the effectiveness of implementing construction projects with APBD funding sources. By understanding the causes of existing problems, corrective steps can be taken to optimize budget use and ensure the smooth running of construction projects. This research can also be a reference for construction researchers and practitioners in similar contexts in other fields.